Heating of nanoparticles in low-pressure plasma jets - Kravchenko, O.Yu.; Maruschak, I.S. (Problems of Atomic Science and Technology, 2022)
The heating of nanoparticles in a low-pressure plasma jet was studied with the help of computer simulation. Modeling of the expansion of a plasma jet with a dispersed phase, which was a mixture of nanoparticles of two sizes, was carried out within the framework of a multi-fluid axisymmetric hydrodynamic model. As a result of the calculations, the spatial distributions of the plasma parameters at different times after the plasma jet injection were obtained. The simulation results show that the temperature of nanoparticles in the plasma jet depends not only on their size, but also on the percentage composition of the mixture of dust particles. The reason for this is the influence of the size of nanoparticles on the spatial distribution of ion concentration, which play a decisive role in the heating of dust particles due to recombination on their surfaces. За допомогою комп’ютерного моделювання досліджено нагрівання наночастинок у струмені плазми низького тиску. Моделювання розширення плазмового струменя з дисперсною фазою, яка являла собою суміш наночастинок двох розмірів, виконано в рамках багаторідинної осесиметричної гідродинамічної моделі. В результаті розрахунків отримано просторові розподіли параметрів плазми в різні моменти часу після інжекції плазмового струменя. Результати моделювання показують, що температура наночастинок у плазмовому струмені залежить не тільки від їх розміру, але й від процентного складу суміші частинок пилу. Причиною цього є вплив розміру наночастинок на просторовий розподіл концентрації іонів, які відіграють вирішальну роль у нагріванні частинок пилу внаслідок рекомбінації на їх поверхні.